John Cleland & Benoit Ferry (eds.): Sexual Behavior and AIDS in the Developing World. - Wimberley, Kristina (Tidsskriftet Antropologi, 1996)
Sexual Behavior and AIDS in the Developing World. Anmeldes af Kristina Wimberley